The Wattpad effect: Developing reading habits through online English stories - Andaresa, Fitara; Rizka, Budi; Asma, Asma (Lembaga Penelitian, Penerbitan, Pengabdian dan Pengembangan Masyarakat (LP4M) Unmuha, 2024)
This study investigates the factors influencing the development of reading habits through online English stories on Wattpad and explores the platform’s associated benefits. Employing a descriptive-qualitative research method, data were collected through in-depth interviews with three active Wattpad users. Purposive and snowball sampling were utilized to select respondents. Data analysis followed Miles, Huberman, and Saldana's (2014) interactive model. Findings indicate that reading frequency, accessibility, diverse genres, and a strong interest to enhance English language proficiency significantly contribute to the formation of reading habits. Participants reported spending 3.5-6 hours weekly on Wattpad, reading 1-3 times per week. Key benefits of using Wattpad include improved language skills, expanded vocabulary, enhanced grammar comprehension, and overall reading proficiency. This study concludes that Wattpad’s accessibility, diverse content, and interactive features effectively facilitate the creation and maintenance of English reading habits.